A Phonological Sketch of Modo: An Endangered Language in Eastern Indonesia - Balukh, Jermy I.; Khairiah, Dewi; Yanti; Maerina, Ryen (Jurnal Arbitrer, 2024)
Modo is an endangered Austronesian language mainly spoken on the islands of Komodo and Rinca in East Nusa Tenggara Province of Indonesia. Despite its status as an endangered language, Modo remains under-documented and understudied. This paper presents a phonological sketch of Modo based on primary data collected from native speakers in our 30-day fieldwork on the two islands. Through careful analysis of recordings from an elicited wordlist and transcription of naturalistic speech, this description covers Modo’s consonant and vowel inventories, syllable structure, stress assignment, and morphophonological analysis. Modo exhibits 31 consonants, including eight prenasalized stops, two implosives /ɓ/ and /ɗ/, the dental plosive /d̪/, the labio-dental approximant /ʋ/, and the loan palatal approximant /j/ and labio-dental fricative /f/. Additionally, Modo has six oral vowels, including the mid-central vowel /ə/, and five nasal vowels. The syllable structure of Modo is predominantly open, though it permits the consonants /h/ and /ʔ/ in word-final positions. Stress in Modo is generally assigned to the penultimate syllable, though shifts can occur in more complex phrases and sentences, indicating a nuanced prosodic system. Modo exhibits limited morphophonological processes, with only deletion and assimilation found in compounding. Furthermore, this study includes a brief discussion on practical orthography to enhance the accessibility of Modo’s unique phonemic units. We suggest the representation of distinctive phonemes, such as the implosives /ɓ/ and /ɗ/, voiced dental /d̪/, labio-dental approximant /ʋ/, and nasal vowels. This phonological sketch not only contributes to the documentation of an endangered language but also clarifies some phonological issues found in previous works and underscores the intricate linguistic features that characterize the Modo language, paving the way for future research and revitalization efforts.